IMPLEMENTASI PENATAAN ASET DAN PENATAAN AKSES DI KELURAHAN TONGOLE KOTA TERNATE: Asset Reform and Access Reform Implementation on Tongole Sub-district Ternate City - Marcel Ridho Juniarto; Endang Pandamdari (Reformasi Hukum Trisakti, 2024)
Implementing agrarian reform activities in the Ternate City Land Office requires a careful balance between asset reform activities and access reform activities in order to create justice in the distribution and utilization of land resources. the formulation of the problem in this article is how the conformity of Asset Arrangement and Access Arrangement of the Agrarian Reform program in Tongole Village, Ternate City with Presidential Regulation No. 86 of 2018? and what are the obstacles faced in the implementation of Asset Arrangement and Access Arrangement in Tongole Village, Ternate City. This research method uses a normative juridical research type that is analytically descriptive, using secondary data types obtained through literature studies and processed qualitatively and then drawing conclusions in a deductive way.  The results of the discussion show that there is an urgent need to improve the implementation of asset management capacity and access management in Tongole Village, Ternate City in accordance with Presidential Regulation Number 86 of 2018. The conclusion is that there are still problems in asset management and access management in Tongole Village, Ternate City. These challenges are in direct conflict with Presidential Decree 86/2018.